The Relevance of Pancasila as the Philosophical Foundation in Law Making in Indonesia - Misno Misno; Ahmad Ahmad; Upik Mutiara (Indonesian Journal of Law and Policy Studies, 2023)
This research explores the relevance of Pancasila as a philosophical foundation in the formation of law in Indonesia. Despite its official recognition as the ideological basis of the state, the practical implementation of Pancasila's values in the legislative process often faces significant challenges. Through a normative empirical approach, this study identifies the gap between the ideal of Pancasila and its application in Indonesian law, particularly in the context of globalization and external pressures. The findings reveal that while Pancasila remains crucial, there is a need for comprehensive reform in the legislative process to ensure that laws genuinely reflect the principles of Pancasila. This research emphasizes the importance of strengthening Pancasila education among policymakers and integrating its values into all stages of law-making to preserve national identity and social justice